2007
DOI: 10.1186/1475-9276-6-15
|View full text |Cite
|
Sign up to set email alerts
|

Using relative and absolute measures for monitoring health inequalities: experiences from cross-national analyses on maternal and child health

Abstract: BackgroundAs reducing socio-economic inequalities in health is an important public health objective, monitoring of these inequalities is an important public health task. The specific inequality measure used can influence the conclusions drawn, and there is no consensus on which measure is most meaningful. The key issue raising most debate is whether to use relative or absolute inequality measures. Our paper aims to inform this debate and develop recommendations for monitoring health inequalities on the basis o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
104
0
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(119 citation statements)
references
References 21 publications
13
104
0
2
Order By: Relevance
“…Although relative risks were consistently higher for the 25 to 64 year olds this reflects their much lower absolute rate of death. This is because relative risks are not independent of the overall rate and will tend to be higher when the absolute rate is low(er) (Houweling et al, 2007). Absolute differences (not shown) were actually higher in the older age group.…”
Section: Resultsmentioning
confidence: 90%
“…Although relative risks were consistently higher for the 25 to 64 year olds this reflects their much lower absolute rate of death. This is because relative risks are not independent of the overall rate and will tend to be higher when the absolute rate is low(er) (Houweling et al, 2007). Absolute differences (not shown) were actually higher in the older age group.…”
Section: Resultsmentioning
confidence: 90%
“…They concluded that there was some empirical evidence that higher relative inequalities were associated with lower overall levels. Houweling et al (2007), in a cross-national analysis of child health, also found that the magnitude of relative differences were empirically related to the overall level of the outcomes. However Houweling et al (2007) also found that absolute inequalities tend to be low at both very high and very low overall levels.…”
Section: Use Of Absolute and Relative Indexes For The Measurement Of mentioning
confidence: 91%
“…Houweling et al (2007), in a cross-national analysis of child health, also found that the magnitude of relative differences were empirically related to the overall level of the outcomes. However Houweling et al (2007) also found that absolute inequalities tend to be low at both very high and very low overall levels. Thus it would appear that there is a strong association between low mortality rates and high relative inequalities, but it is not impossible to achieve a reduction in relative rates when overall mortality rates are falling.…”
Section: Use Of Absolute and Relative Indexes For The Measurement Of mentioning
confidence: 91%
“…A frequently suggested explanation has been the tobacco epidemic [45,48,49]. Educationbased inequalities in tobacco use are still increasing, and these increases vary between men and women [48,50], which might partly explain the trends we found [39,43,51]. The delayed and lower uptake of tobacco use among women compared with men may explain the weaker increase in e 65 among less-educated women from the 1980s and thereafter.…”
Section: Explanation and Interpretation Of Our Resultsmentioning
confidence: 77%